Effect upon the growth and yield of crop plants, of environmental conditions while in the seedling stage - Sofajy, Salim Abdulah (The University of Edinburgh, 1974)
The provision of optimum conditions for the growth of seedlings, even at high cost for short periods, has proved to be of benefit when growing plants under adverse circumstances. Techniques have been evolved to suit the production of lettuce over winter under glass, and the early spring rearing of young tomato plants. A series of experiments was undertaken to evaluate the use of such methods in the cultivation of radishes in the greenhouse under the low levels of natural daylight obtaining in the months from October to March. Plants which were given, from the moment the cotyledons unfolded, a few days of a 20 hour, 12000 lux, photoperiod at temperatures of 22°G. were found to have grown faster and become 1 argAT during the subsequent period in the greenhouse than those which spent the entire time in the greenhouse. The total dry matter gain in the radish was found to be related to the extent of the light treatment given. The varieties of radish used in the experiment did not initiate flowers as a result of the treatment received, thus allowing them to form bulbs. The longer the period spent in the cabinet the greater the size of the bulb produced. Analysis of the pattern of growth indicates that this is entirely due to the treated plants achieving a faster rate of growth at an earlier stage. In particular the fast rate of increase in leaf area of treated plants may be held to contribute largely to this. The treatment need not be given immediately after germination of the seed. It could be delayed up to eight days without significantly affecting yield. The time spent in the cabinet is the important factor. The contribution of the cotyledons is demonstrated by the fact that if only one is removed the remaining one grows to a larger size, but when both are removed no such compensatory effect is observed in the true leaves and yields are lowered. The shading of one or both cotyledons also markedly reduced yield. The size and the number of the cells in the cotyledons was shown to be increased with increasing light intensity but the duration of the period of cell enlargement was not affected. I.A.A. application to the hypocotyl increased the size of the radish bulbs and the net assimilation rate of the plant. The growth and respiration changes observed seemed to be related to the supply of carbohydrate at different levels of light intensity. The differences in photosynthetic pigments observed were consistent with those expected as a response to mutual shading. Throughout the environmental work the quantity of light received was the predominant factor in limiting yield. There was no evidence that application of high levels of phosphate could compensate for a reduction in the amount of light given. It was considered that the greatest potential for increasing bulb yield was to use treatments which raise the N.A.R. either by increasing day length or light intensity or both, or to supply I.A.A. to the hypocotyl.
The effect upon the growth and yield of crop plants, of environmental conditions while in the seedling stage
Keywords: crop plants; growth of crop plants; yield of crop plants; environmental conditions; seedling stage; optimum conditions; growth of seedlings; lettuce; tomato; radish; cotyledons; photosynthetic pigments; phosphate; N.A.R.; I.A.A.; hypocotyl; bulb yield; day length; light intensity; shading